2022
DOI: 10.3389/fmed.2022.906140
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Physiological Index Changes and Safety Work of Female Medical Staff With Different Medical Protection Standards in the Ward of COVID-19

Abstract: BackgroundEffective personal protective equipment (PPE) contribute to the prevention of COVID-19 infection. However, it is necessary to evaluate the potential risk of different medical protections in the isolation ward of COVID-19.ObjectivesWe aimed to explore the dynamics in physiological indexes of medical staff under primary and secondary PPE in the isolation ward of COVID-19 and provide the scientific basis for determining the safe work strategy.Materials and MethodsIn this study, 30 female nurses were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Unlike the outdoor environment, medical staff operate within confined spaces controlled by climate, whereas the ambient indoor environment and body heat dissipation affect the microclimate temperature of medical staff clothing, causing fatigue and decreased work efficiency. A recent investigation 17 has suggested that for heavy work, wearing MDPC should not exceed 40 min for continuous safe work, while for light work, this duration can be extended to 110 min to ensure safety.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the outdoor environment, medical staff operate within confined spaces controlled by climate, whereas the ambient indoor environment and body heat dissipation affect the microclimate temperature of medical staff clothing, causing fatigue and decreased work efficiency. A recent investigation 17 has suggested that for heavy work, wearing MDPC should not exceed 40 min for continuous safe work, while for light work, this duration can be extended to 110 min to ensure safety.…”
Section: Introductionmentioning
confidence: 99%